Pendidikan Seks yang Sehat untuk Anak-Anak - Harry Suherman (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
Although the issue of sexual behavior has been existed for centuries but it is always interesting when it comes out in a discussion. This is understandable since sex is the human basic need and humans exist because of sex. Therefore sex and human beings are inseparable. Nevertheless, sex behavior must be controlled and with appropriate direction, especially for young generation who are living in a challenging environment. The controls for sex behavior include moral, religion, and information about healthy and responsible sex behavior. Sexual behavior is intended to build physiological, psychological, social spiritual, and procreative partnership between man and woman. The meaning of sexuality is larger than just intimate behavior between man and woman which is merely a biological interaction; it is a reflection of total human relations. Sexuality is personal relations based on commitment of love and loyalty.Key words: Sexual, Health, Children and Adolescents, Responsibility